Pengaruh Leverage, Firm Size Dan Voluntary Disclousure Terhadap Earnings Response Coeffisient (ERC): Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ratna Wijayanti Daniar Paramita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2012)
Earnings information is the most responded by investors because it provides a de- scription of the company’s performance, but information alone is sometimes not enough profit to serve as the basis for decision making of investors because it is possible the information is biased, to measure the level of profit, can use a variable Earnings Response Coefficient (ERC.) The strong market reaction to earnings in- formation reflected in the high earnings response coefficients (Earnings Response Coefficient) or ERC, if earnings are reported to have a response force (power of response). then that reported earnings quality. The purpose of this study was to identify the effects of direct and indirect size, and earnings response disclousure voluntary coeffisient (ERC) This research examined 20 manufacturing companies listed on the Indonesia Stock Exchange-year period 2005-2009. Statistical methods used to test the hypothesis is Structural Equation Model (SEM) with AMOS version 18. The empirical results of this research: leverage has no significant effect on the Earnings Response Coefficient (ERC). Against the influence of voluntary disclou- sure to Earning Response Coefficient (ERC) have positive test results significantly. Similarly, for the effect of the Size to voluntary disclousure have significant posi- tive results. The results of this study also proves there is no significant effect of Size to Earnings Response Coefficient (ERC). Voluntary disclosure in this study is an intervening variable for the indirect effect between the size of Earnings Response Coefficient (ERC).